Maintenance program management of npp emergency protection systems - Saveleva, Oksana; Stanovska, Iraida; Bibik, Tymofiy; Berezovska, Ekaterina (Eastern-European Journal of Enterprise Technologies, 2016)
It is found that the maintenance of a specified performance of NPP emergency protection systems is a risky program which consists of individual projects in accordance with the maintenance plan. To prevent risk situations and reduce their negative consequences, a mathematical model of the probability of catastrophic events at NPP is constructed. In accordance with the Shewhart – Deming cycle, a plan of project activities in case of risk events that may lead to an emergency is developed. It is also found that the main attributes of the qualification maintenance program of the NPP EPS equipment are the mission and goal of the program management, as well as time and resources of the projects that make up the program. The sensitivity of the goals to uncertainties (risks) that accompany the program life cycle is confirmed. A master plan of project activities in accordance with the Shewhart – Deming cycle is developed and supplemented by the extraordinary stage “Action”, the transition to which can occur from each of the four “normal” stages, namely from the stage of the cycle at the beginning of the negative external event.